Yolk free egg substitute improves the serum phospholipid profile of mice with metabolic syndrome based on lipidomic analysis - Zhihui Yu; Lingyu Fan; Fei Tai; Lixin Zhang; Xiaoyu Zhang; Yisheng Chen (Food Science and Human Wellness)
In this study, the impacts of egg consumption on mice model of metabolic syndrome (MetS) were comparatively investigated. Mice were divided into five groups (n=8): normal diet group (ND), high-fat diet group (HFD), HFD with whole egg group (WE), HFD with free-yolk egg substitute group (YFES), and HFD with lovastatin group (Lov). Main biochemical indexes and a non-targeted lipidomic analysis were employed to insight the lipid profile changes in serum. It was revealed that WE could significantly improve serum biochemical indexes by reducing body weight, low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC), while increasing high-density lipoprotein cholesterol. YFES exhibited remarkably better performance in increasing phosphatidylglycerol and phosphatidic acids, while decreasing phosphatidylinositol than WE. A total of 50 differential lipids biomarkers tightly related to glycerophospholipids metabolism were screened out. Carnitine C18:2 and C12:1, SM (d18:0/12:0), and SM (d18:1/14:1) were significantly upregulated in YFES compared to WE. YFES reduced expression of SREBP-1c and Cpt1a, while did not affect the expression of PPAR-α. Sphingomyelin biomarkers were positively related to the TC (|r| > 0.6), while PPAR-α was negatively correlated with triglyceride and LDL-C levels. To sum up, YFES attenuated HFD-induced MetS by improving the serum phospholipids, which account for its modulation of glycerophospholipid metabolism.